Urban Defense Index for City Branding: A Case Study of Five Cities in Kalimantan - Wadjdi, Achmad Farid; Namora , Yan; Rahardjo , Eko; Holdun, Moh Ibnu (Journal of Developing Economies, 2023)
This paper proposes a new model of urban security for city branding in Indonesia, which aims to address the gap in city branding indices lacking safety and security factors. The proposed model, the Urban Defense Index (UDI), measures a region's ability to manage risks and handle security threats in urban areas. The UDI is calculated based on three sub-indices: ThreatsDisruptions- Obstacles- Challenges (TDOC), Posture, and Stability, which use objective and subjective measurements. A case study uses the proposed model to measure five Kalimantan cities' urban defense readiness levels. The study found that Stability, Posture, and TDOC are essential factors in determining the level of urban defense readiness in the cities. Future research can address the limitations of the UDI model proposed in this study and expand the UDI model to include other factors that affect urban security.